Mediasi Pidana dalam Ketentuan Hukum Pidana Adat - Trisno Raharjo (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research focused to dispute resolution through negotiation in “Adat” Law. This research operates in “adat” community of Banjar, Aceh, Ambon, North Lombok, and Lamaholot. The researched question is penal mediation as conflict resolution between perpetrator and victim of criminal conduct. Using normative, conceptual, and historical approach, this research reveals negotiation becomes the basis conflict dispute between perpetrator and victim. Negotiation inspired the development of criminal mediation which is known as traditional village or tribal moots.Key words : Criminal Mediation, “adat” penal law, “adat” community